Tingkat Kesadaran dan Kepedulian Siswa SMA Negeri 1 Talaga terhadap Lingkungan Sekitar (International Forum of Researchers and Lecturers, 2024)
The 21st century can be said to be a century of change and progress in various fields. This article aims to examine the potential of environmental awareness and concern into 21st century education. Environmental awareness is the awareness that a person has in protecting the environment, this environmental awareness is reflected through attitudes and responsibilities in protecting the environment. In its application, it is inseparable from various challenges such as the value of good environmental awarness.